Identification of Dermatophyte Fungi Causing Tinea Pedis And Tinea Unguium In Malabero Coastal Communities, Bengkulu - Mardhatillah Sariyanti; Putri Maya AGustria; Willujeng Fanny Herlambang (Microbiology Indonesia, 2021)
Dermatophytosis cases have increased significantly in various countries, more than 20-25% of the population were infected by superficial fungal infections. Malabero urban village is a coastal area in Bengkulu city with high temperature and humidity. The daily activities of residents in the area are mostly fishermen, so they are in a watery or wet environment for approximately 12 hours every day. So, this research aimed to identify dermatophyte fungi that caused tinea pedis and tinea unguium from these coastal communities. The diagnosis of tinea was based on symptoms and physical examination of the lesion area. Furthermore, specimen collection was carried out by scraping the lesion area, then examined with 20% KOH and fungal culture on sabouraud dextrose agar media. Subjects included 79 people who had symptoms of tinea pedis and 33 people with symptoms of tinea unguium. The results of dermatophyte fungi identification were obtained, Trichophyton mentagrophytes, Trichophyton rubrum, Trichophyton tonsurans, and Aspergillus sp. Our conclusion is the most identified dermatophyte species is Trichophyton mentagrophytes. Keywords: Coastal, dermatophyte, tinea pedis, tinea unguium